Numerical Study of an Ejector as an Expansion Device in Split-type Air Conditioners for Energy Savings - Sumeru, Kasni; Sulaimon, Shodiya; Ani, Farid Nasir; Nasution, Henry (ITB Journal Publisher, LPPM ITB, 2013)
The present study describes a numerical approach for determining both the motive nozzle and constant-area diameters of an ejector as an expansion device, based on the cooling capacity of a split-type air-conditioner using R290 as refrigerant. Previous studies have shown that replacement of HCFC R22 with HC290 (propane) in the air conditioner can improve the coefficient of performance (COP). The purpose of replacing the capillary tube with an ejector as an expansion device in a split-type air conditioner using HC290 is to further improve the COP. In developing the model, conservation laws of mass, momentum and energy equations were applied to each part of the ejector. The numerical results show that the motive nozzle diameter remains constant (1.03 mm) under varying condenser temperatures, whereas the diameter of the constant-area decreases as the condenser temperature increases. It was also found that improvement of the COP can reach 32.90% at a condenser temperature of 55 Â°C. From the results mentioned above, it can be concluded that the use of an ejector can further improve the COP of a split-type air conditioner using HC290 as working fluid.